Digital Entrepreneurship and Marketing Responsibility: A Bibliometric Analysis - Susilowati, Susilowati - (Journal of Innovation and Applied Technology, 2025)
This paper conducts a bibliometric analysis to explore the relationship between digital entrepreneurship and marketing in today's business environment.  It highlights how digital technologies and online platforms have revolutionized both entrepreneurial and marketing strategies, underscoring the importance of ethical and social responsibility. The aim is to uncover research patterns, predominant themes, and gaps in the existing literature, providing insights into how digital entrepreneurial ventures can support ethical and sustainable economic development. The analysis also considers how marketing responsibility is integrated into digital business strategies as a mechanism for creating value for various stakeholders. It discusses the impact of technologies like big data and AI on targeted marketing and the ethical issues related to data privacy. The findings stress the need for businesses to adopt innovative marketing techniques that comply with strict ethical standards and sustainability goals.